Anti-Nepotism Reconsidered: The Case of Husband and Wife Employment - Werbel, James D.; Hames, David S. (Group & organization management, 1996)
This investigation examines employees' perceptions of paired employees-dual-career couples who work for the same organization. It examines the effects of individual differences (spouse employment status, supervisory role, and gender) and one situational difference (organizational size) upon employees' attitudes toward paired employees (PEs). The sample for this study was derived from people who traveled through a regional airport. The results suggest that males, supervisors, and employees in small organizations had negative attitudes regarding paired employment or were less willing than their counterparts to hire PEs. These findings are discussed in terms of policy implications for managing PEs.